SISTEM PENGENDALIAN INTERN PEMERINTAH (SPIP) ATAS SISTEM AKUNTANSI KAS UMUM NEGARA (SAKUN) (Studi Pada Kantor Pelayanan Perbendaharaan Negara Surabaya I) - Maulida, Oktaviyani Nurul (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to find out and to evaluate the government internal control system over the general state treasury accounting system (SAKUN). The research paradigm is positivistic with qualitative approach. The result of analysis shows that the implementation of government internal control system is quite good when it is seen from the organization structure, control environment, communication and information, aspects as well as monitoring. The government internal control system has implemented the regulation reference of the Director General of the Treasuryâs decision No KEP-34/PB/2013 of the Governance Implementation of Internal Compliance Tasks within Directorate General of Treasury Environment. Nevertheless, there is a little chance of error in the process of general state treasury accounting system (SAKUN). Moreover, monitoring in its implementation is required by the management department of Work Unit. In general it can be concluded that the internal control system is quite good and each employee understand the regulation of internal control system which has been determined by the Government.Keywords: Government Internal Control System, the General State Treasury Accounting System (SAKUN), Internal Compliance Unit (UKI).